SHEAR WAVES IN LONGITUDINAL PERIODICAL WEAK-INHOMOGENEOUS LAYER - Belubekyan, M.V.; Sahakyan, S.I.; Hunanyan, A.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2015)
In thе paper characters of propagation of elastic waves in layer with continuously changing periodical heterogeneity along layer are investigated. Numerical results of dependence of wave propagation phase velocity from determining parameters of heterogeneity of wavelength are shown.